2020
DOI: 10.1021/acsomega.0c02301
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable SERS Detection by Hybrid Cu2O/Ag Nanospheres

Abstract: Cu 2 O nanospheres (NSs) were synthesized by modifying the glucose reduction method. Based on this method, Cu 2 O/Au (Ag) NSs were further prepared by in situ reduction of HAuCl 4 (via electron beam evaporation of Ag). With Rhodamine 6G (R6G) as probe, the surface-enhanced Raman scattering (SERS) characteristics of the three samples were systematically studied. The experiment results showed that the enhancement factor (EF) of Cu 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Introducing Ag NWs into the Cu 2 O‐CuO film makes it possible to form a new charge transfer (CT) system due to the Fermi level of Ag being lower than the surface state energy level of CuO and Cu 2 O. The Fermi energy levels of Ag, CuO, and Cu 2 O are 4.26 eV, [21] 5.3 eV, [31] and 4.84 eV, [21] respectively. When an Ag NW is in contact with a p‐type semiconductor such as CuO or Cu 2 O, the charge distribution is readjusted to reach equilibrium of the Fermi level between Ag and Cu 2 O (or CuO).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Introducing Ag NWs into the Cu 2 O‐CuO film makes it possible to form a new charge transfer (CT) system due to the Fermi level of Ag being lower than the surface state energy level of CuO and Cu 2 O. The Fermi energy levels of Ag, CuO, and Cu 2 O are 4.26 eV, [21] 5.3 eV, [31] and 4.84 eV, [21] respectively. When an Ag NW is in contact with a p‐type semiconductor such as CuO or Cu 2 O, the charge distribution is readjusted to reach equilibrium of the Fermi level between Ag and Cu 2 O (or CuO).…”
Section: Resultsmentioning
confidence: 99%
“…For Ag‐Cu 2 O‐MBA system (see Figure 7a), the electrons of “new Fermi level” of Ag NWs excited by incident laser will inject into the conduction band (CB) of Cu 2 O and migrate towards lower energy levels (the surface‐state energy level E ss ) of Cu 2 O [3,34] . Meanwhile, the electrons on the valence band of Cu 2 O can only transfer to lower energy levels than CB because laser excitation energy (1.96 eV) is lower than the band gap (2.2 eV) [21] . As a result, these photoexcited electrons of Cu 2 O will be transferred into LUMO of the 4‐MBA molecules instead.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EF at 610 cm −1 was 3.99 × 10 10 . In comparison with other kinds of materials, we listed their EFs [ 15 , 16 , 17 , 18 , 19 , 29 ] in Table 1 . It was found that the EF of our proposed substrate was the highest, indicating that the Ag@CuO FM substrate achieved excellent SERS performance.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, precious metals are not the best choice for surface enhanced Raman scattering (SERS) substrate. It was documented that semiconductor nanomaterials (SNs) such as ZnO [ 15 ], Cu 2 O [ 16 ], and CuO [ 17 , 18 , 19 ] also produce weak SERS signals. The composite structure of precious metals and semiconductor nanomaterials has a better effect on SERS [ 20 ] because it has not only the electromagnetic enhancement effect between precious metal nanoparticles, but also the chemical enhancement one produced by SNs.…”
Section: Introductionmentioning
confidence: 99%